The Effect of Volume Fraction Variation on The Mechanical Properties of Epoxy-based Sugarcane Fiber Composites - Anisa Fitri; Bayu Prasetya; Muhammad Yasin Siregar; Ahmad Andryan Prakoso; Wahyu Solafide Sipahutar (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
The use of natural fibers as reinforcement in composite materials offers an environmentally friendly alternative to synthetic fibers. Among them, sugarcane fiber (bagasse), an agro-industrial byproduct rich in cellulose, hemicellulose, and lignin, holds considerable potential but remains underutilized. This study aims to evaluate the effect of varying sugarcane fiber volume fractions (50%, 60%, and 70%) on the mechanical properties of epoxy resin-based composites. The composites were fabricated using the hand lay-up method, followed by mechanical testing including tensile tests (ASTM D3039) and bending tests (ASTM D790). The results showed that the highest tensile strength of 26.43 MPa was achieved by the E70 sample, while the E50 sample exhibited the highest bending strength at 142.53 MPa. Fractographic analysis revealed that structural defects such as voids, fiber pull-out, and debonding significantly influenced the mechanical performance of the composites. While fiber volume fraction has a notable impact on tensile and bending strengths, the relationship is not strictly linear due to variations in fiber-resin distribution and interfacial bonding quality. These findings suggest that sugarcane fiber-based epoxy composites, particularly with a 50% volume fraction, have strong potential for application in lightweight structural components, furniture panels, or automotive interior parts. Future research may focus on improving interfacial bonding through chemical treatments or hybridization with other natural fibers to further enhance performance.